An Improvement on the End-of-Life of High-Speed Rail Rolling Stocks Considering CFRP Composite Material Replacement - Rungskunroch, Panrawee; Kaewunruen, Sakdirat; Shen, Zuo-Jun (Frontiers in Built Environment, 2019)
It is undeniably true that transportation systems positively impact human life but, the use of transportation systems also emits greenhouse gasses in the environment which leads to global warming. In this day and age, various technologies are being combined with transportation systems, aimed at reducing the global impact of greenhouse gas emissions. The high-speed rail (HSR), which is well-known for low CO2 emissions, has continually been improved, especially its model. In this study, the material replacement method is taken to account for a feasibility study on the next model of the HSR. There are three types of composite materials that consist of glass filled with epoxy, glass filled with polyester and glass filled with nylon, replacing the six chief parts of HSR components. As a result, the total weight of rolling stock has significantly reduced to 24.61% on average so, it can decrease the amount of fuel in the HSR operation. Also, the feasibility of the recyclability (%Rcyc) and recovery rate (%Rcov) is critical in judging the suitability of the replacement. The research found that the replacement of CFRP (Carbon fiber reinforced polymer) generates a positive result on %Rcyc value at 73.9% compared with 61.4% in the original model. Besides, the %Rcov at 78.9% is higher than the 73.1% of the original model.